The Comparison of Financial Perfomance Between PT. Unitex TBK and PT. Sunson Textile Manufacturer TBK by Using Financial Ratio Analysis: Perbandingan Kinerja Keuangan Antara PT. Unitex TBK dan PT. Sunson Produsen Tekstil TBK dengan Menggunakan Analisis Rasio Keuangan - Stefvy; Deva Djohan; Robin; Ester; Duffin (Universitas Muhammadiyah Palu, 2024)
The writer’s purpose of making this research is to compare PT. Unitex Tbk and PT. Sunson Textile Manufacturer Tbk of which company performs better during the tight competition of textile industries since the ASEAN-China Free Trade Agreement is signed in 2010. The object of this research is PT. Unitex Tbk and PT. Sunson Textile Manufacturer Tbk which are focusing on producing textile products such as yarn, fabric and other textile products. The objective of this research is to see the role of financial ratio analysis of both companies. The writer collects the data by using internet.After analyzing the data of both companies, the writer found out that both companies had a low perfomance during year 2018-2022. But, by comparing at this financial condition and performance on both companies, therefore, the writer can conclude that PT. Sunson Textile Manufacturer Tbk has a better financial performance.